Experimental, Spectroscopic, Computational and Molecular Studies of Plant Growth Promotor 2-Naphthylacetic Acid - Mir, Mohd Amin; Mahmoud, Maythem; Andrews, Kim; Nayak, Arunima; Kukretee, Nupur; Kotnala, Shreya (Physics and Chemistry of Solid State, 2025)
The bioactive compound 2-Naphthylacetic Acid was the subject of theoretical experiments using DFT-B3LYP techniques with 6-311++G(d,2p) basis sets. Computational analysis included the calculation of 2-Naphthylacetic Acid's geometrical parameters, molecular characteristics, and vibrational spectra. Density Functional Theory was used to carry out geometrical optimizations. When the calculated vibrational spectra and optimized molecular geometry were matched to experimental results, significant agreement was found. Furthermore, for the aforementioned compound, DFT characteristics like, chemical hardness, total energy, chemical potential, and electrophilicity were calculated. The relative stability and reactivity of the compounds under study were predicted using these descriptors.